A randomized controlled trial adding behavioral counseling to supervised physical activity in people living with and beyond cancer (BOOST-UP-): a study protocol for a live remotely-delivered behavior change intervention - Linda Trinh; Ryan E. Rhodes; Shabbir M. H. Alibhai; Kristin L. Campbell; David M. Langelier; Eugene Chang; Tracey Colella; Brian Chan; Daniel Santa Mina; Paul Oh; Edward McAuley (BMC Cancer)
Abstract Background For many people living with and beyond cancer (LWBC), physical activity (PA) declines significantly after supervised PA interventions. The effect of short-term, supervised PA interventions on motivational outcomes and longer-term PA in people LWBC is limited, especially theoretically-based approaches to identify key motivational outcomes for behavior change. The purpose of this study is to compare the effects of a 6-month virtual supervised PA group plus standard exercise counseling (PA + EC) versus a virtual supervised PA plus motivationally-enhanced behavioral counseling (PA + BC) group on moderate-to-vigorous intensity PA (MVPA) in people LWBC. Methods This study is a two-armed, multi-site randomized controlled trial (RCT). People LWBC will be recruited and randomized to a 6-month virtual supervised PA intervention plus standard exercise counseling (PA + EC group; n = 118) or a 6-month virtual supervised PA plus behavioral counseling based on the Multi-Process Action Control (M-PAC) framework (PA + BC group; n = 118). Supervised PA will be delivered via synchronous Zoom classes that tapers to a home-based protocol at the end of the study. The goal of both groups is to gradually increase PA to the cancer PA guidelines (e.g., 90 min of MVPA/week). The PA + BC group will receive twelve behavioral counseling sessions with a qualified exercise professional (QEP), and the corresponding counseling session will be delivered bi-weekly. The behavioral counseling sessions will be based on the M-PAC’s reflective, regulatory, and reflexive processes. In addition to the supervised PA classes, the PA + EC (i.e., attention control group) will receive twelve standard PA counseling sessions based on PA training principles. People LWBC will complete measures at baseline, midpoint, post-intervention (6-months), at 6-months follow-up, and 1-year follow-up. Self-reported measures include quality of life (QoL), motivational outcomes, health economics, and patient satisfaction. Objective measures include PA via accelerometry. Multilevel modelling will examine change in the primary (i.e., PA) and secondary outcomes (i.e., motivational outcomes from the M-PAC, physical function, QoL) at the five time points. Discussion This study will create greater understanding on efficacious programming to support PA maintenance that can be used by clinical and community-based organizations as a low-cost, supportive care tool to improve health outcomes for people LWBC. Trial registration Clinicaltrials.gov ID NCT06624930.